Level of knowledge on environmental issues and enviromental education of primary schools' headmasters in Kuala Lumpur, Malaysia - Khalid, Ika Liana; Harun, Rosta; Muda, Azizi; Ismail, Ismi Arif (IDOSI Publications, 2011)
This study focuses on the level of knowledge on various environmental issues and environmental education carried out on 30 primary schools’ headmasters in Kuala Lumpur. A set of questionnaire which comprised of 20 questions was applied as the instrument for data collection. The result reveals that the headmasters’ level of knowledge on environmental issues and environmental education is overall moderate (Mean score = 69.5%, S.D = 16.83). The study also finds that headmasters are more sensitive to environmental issues that are locally present such as extinction of animals and haze, but are less sensitive to issues that do not happen locally such as the El Nino phenomenon. This is due to less exposure and due to little understanding on these issues. In terms of knowledge of environmental education, this study finds that headmasters are less aware to the national implementation of cross-curriculum environmental education in schools. Cross curriculum environmental education has been moderately implemented in Malaysian schools in Malaysia since 199. Results of the study are used by the Curriculum Development Centre, the Institute of Aminuddin Baki (IAB) and the Department of Environment (DOE) to design courses for headmasters to manage environmental education in schools.